Zn doping induced band gap widening of Ag2O nanoparticles - De, A.K.; Majumdar, S.; Pal, S.; Kumar, S.; Sinha, I. (Elsevier Ltd, 2020)
Semiconductor bandgap widening is a little investigated phenomenon in photocatalysis literature. The present investigation attempts the widening of the narrow bandgap of Ag2O to make it a semiconductor with more attractive properties. The synthesis of Zn doped Ag2O nanostructures followed a typical hydrothermal synthesis procedure. An increase in the lattice parameters of Ag2O with doping indicated the occupation of an interstitial position by the dopant metal ion. Density functional theory calculations also demonstrated the expansion of the Ag2O crystal lattice with the dopant at an interstitial location. The bandgap of the Ag2O increased to 1.65 eV for 5-mol percent doping. The DFT calculated density of states (DOS) plots also exhibit an increase in the bandgap of Ag2O after Zn doping. These doped Ag2O nanoparticles were useful in photocatalysis of methyl orange degradation under visible light irradiation. © 2020 Elsevier B.V.
Keywords: Hydrothermal synthesis; Doping; Bandgap widening; DFT calculations; Photocatalysis